A new pterosaur tarcksite from the Upper Cretaceous Candeleros Formation, Neuquén Province, Patagonia, Argentina - Heredia, Arturo Miguel (2021)
New pterosaur tracks from the Aguada de Tuco tracksite of the Cenomanian Candeleros Formation (Neuquén Basin, Argentina) are reported here. They are preserved in medium grain-sized sandstones from fluvial deposits and are associated with Arenicolites isp. The pterosaur tracks are preserved as concave and convex epirelief, as true tracks and natural casts, respectively. The manus impressions, which are the most abundant, are usually isolated, although manus-pes sets and sequences of manus-manus imprints, some of them probably representing trackways, have been also documented. The best-preserved manus tracks (average 10.8 cm long, 5.4 cm wide) are tridactyl and strongly asymmetrical. The pes tracks (average 11.5 cm long, 4.8 cm wide) are very elongated, trapezoidal to subtriangular, and generally preserve three-digit impressions. Some morphological track variabilities, such as elongated impressions of manus digit III, has been interpreted as the result of variations in substrate properties, mainly moisture content, and behavior. The main features of the studied tracks, manus and pes track morphologies and length/width ratios, are similar to those of the Pteraichnus ichnogenus. Nevertheless, due to their preservation, not optimal, we classify them as cf. Pteraichnus isp. Only other site with pterosaur tracks has been found in the early Late Cretaceous of South America. These tracks are also in the Candeleros Formation but differ from the Aguada de Tuco ones in having differences in divarication of manus digit impressions, among other features. The present study contributes to the knowledge of the poorly pterosaur track record from Gondwana and its ichnotaxonomic and paleoecological implications.